Thermal runaway behavior and hazard evaluation of cumene hydroperoxide mixed separately with four products under adiabatic conditions coupled with risk matrix method. Issue 2 (21st September 2021) - Yu, Chang‐Fei; Liu, Shang‐Hao; Wang, Wen‐Tao; Xu, Rui‐Jie
Abstract: Runaway reactions of organic peroxides (OPs) are a significant issue in process safety, due to their fragile bonds and extensive heat release during abnormal conditions. As one of the typical OPs and an intermediate in the process of producing phenol, cumene hydroperoxide (CHP) is likely to mix with its products and lead to an uncontrollable self‐accelerating decomposition reaction. In this study, the thermal hazard of CHP mixed with four products separately was evaluated and identified using accelerating rate calorimeter technology. Experimental data illustrated that the maximum pressure rise rate had greatly increased from 1.1 to 15.5, 18.3, and 41.5 bar min −1, and the maximum self‐heating rate had dreadfully raised from 5.4 to 107.7, 116.9, and 231.0°C min −1, when CHP mixed with its products from methanol to phenol, acetophenone, or dimethylphenyl carbinol, respectively. These phenomena indicated a precarious and dangerous reaction decomposition mechanism of CHP after its products mixed under runaway conditions. This work is expected to help researchers and even industrial workers to better identify the potential thermal hazard of CHP in the presence of products; in particular, experimental and calculated parameters are necessary for the appropriate choice of safe conditions of application, waste disposal, storage, and transportation of CHP.